1988
DOI: 10.1161/01.hyp.12.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Age and blood pressure changes. A 20-year follow-up study in nuns in a secluded order.

Abstract: In a prospective study, 144 white nuns belonging to a secluded monastic order and 138 white control laywomen were followed for 20 years to investigate whether living for a long time in a stress-free environment influences the effect of aging on blood pressure. Silence, meditation, and isolation from society are the distinctive features of the life-style examined. At study entry, blood pressure was not dissimilar in the nuns and the control group, but it increased over time only in the controls, with a mean slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 20 publications
4
45
0
2
Order By: Relevance
“…The lack of BP rise in nuns may be related to seclusion and to 'peaceful', stress-free, monastic environment, characterised by silence, meditation and isolation. 3 The present study also suggests that the difference between admission (and possibly 'stressed') BP and followup (after in-patient stay) BP levels was significantly related to sodium intake (as reflected by urinary sodium to creatinine ratio). The 'restrictiveness' of the hospital environment has previously been reported to influence BP in psychiatric in-patients.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The lack of BP rise in nuns may be related to seclusion and to 'peaceful', stress-free, monastic environment, characterised by silence, meditation and isolation. 3 The present study also suggests that the difference between admission (and possibly 'stressed') BP and followup (after in-patient stay) BP levels was significantly related to sodium intake (as reflected by urinary sodium to creatinine ratio). The 'restrictiveness' of the hospital environment has previously been reported to influence BP in psychiatric in-patients.…”
Section: Discussionsupporting
confidence: 62%
“…[3][4][5] The reasons why these groups have lower blood pressures are uncertain and studies attempting to identify those factors 'protecting' them may help to identify the environmental factors causing high BP.…”
Section: Introductionmentioning
confidence: 99%
“…Of those, 36 (57%) reported lower BP or less hypertension in those who were more R/S, whereas seven (11%) reported higher BP. When examining the higher quality studies (those rated 7 or higher on a 1-10 scale), 24 (62%) reported lower BP or less hypertension among those who were more R/S [161][162][163][164][165][166][167][168][169][170][171][172][173] or in response to a R/S intervention [174][175][176][177][178][179][180][181][182][183][184] (including two reports from a single study, one reporting results for the overall sample and one for the sample stratified by race). In contrast, seven studies reported higher blood pressure among the more religious, including two lower quality studies [185,186] and five high-quality studies (13%) [187][188][189][190][191].…”
Section: Hypertensionmentioning
confidence: 99%
“…Il semble qu'elle l'abaisse, mais à court terme seulement si le stress dé-clenchant n'est pas éliminé. Une étude prospective sur plus de 20 ans est intéressante à cet égard, qui a comparé les tensions artérielles de soeurs dans un couvent, au calme, à celles de femmes de même âge vivant dans des conditions moins tranquilles [3]. Comme prévu, l'hypertension n'est pas devenue le problème des soeurs, mais bien du groupe témoin.…”
Section: Stress Et Relaxationunclassified